Multi-solid waste-based artificial stone and preparation method thereof

By preparing multi-solid waste-based artificial stone and utilizing spherical particles of iron tailings powder, fly ash and steel slag powder in combination with activators and enhancers, the problems of low solid waste utilization and insufficient artificial stone performance were solved, achieving efficient and environmentally friendly resource utilization and performance improvement.

CN120574011BActive Publication Date: 2025-09-26TIANJIN METALLURGICAL SPECIAL MATERIALS CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511099431.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-08-07
Publication Date
2025-09-26
Estimated Expiration
2045-08-07

AI Technical Summary

Technical Problem

In the existing technology, solid wastes such as iron tailings and fly ash are not fully utilized, and the artificial stone preparation process has problems such as low resource utilization, long production cycle, and insufficient mechanical properties, resulting in environmental pollution and waste of resources.

Method used

Iron tailings powder, fly ash, steel slag powder and water are mixed to form spherical particles, activators and reinforcing agents are added, and multi-solid waste-based artificial stone is prepared through pressing, molding and curing. The activator is used to activate the mineral activity, and the reinforcing agent is used to improve the hydration reaction rate and strength.

Benefits of technology

It achieves efficient utilization of solid waste, reduces production costs, improves the toughness, strength and wear resistance of artificial stone, reduces environmental pollution and shortens the preparation cycle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120574011B_ABST
    Figure CN120574011B_ABST
Patent Text Reader

Abstract

The present invention provides a multi-solid waste-based artificial stone and a preparation method thereof, comprising the following steps: Step 1 is to uniformly mix iron tailings powder, fly ash, steel slag powder, and water, and then crush and roll to obtain spherical particles; Step 2 is to uniformly mix the spherical particles, steel slag powder, fly ash, cement, an activator, and a reinforcing agent with water to obtain a wet material; Step 3 is to press and shape the wet material, and cure it to obtain the multi-solid waste-based artificial stone. The multi-solid waste-based artificial stone of the present invention utilizes iron tailings, steel slag, and fly ash to prepare the artificial stone, which not only consumes a large amount of various solid wastes, reduces the amount of natural sand mined, reduces the amount of pollutant gas emissions generated by the sintering of cementitious materials, and improves the ecological environment; at the same time, after the action of the activator and reinforcing agent, the artificial stone can quickly undergo a hydration reaction in a short period of time to generate gel products such as silicic acid and aluminic acid, reduce the internal pore structure, and improve the density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of building materials, and in particular relates to a multi-solid waste-based artificial stone and a preparation method thereof. Background Art

[0002] With the rapid development of industry, the discharge of solid wastes such as iron ore tailings, steel slag, and fly ash has increased year by year. The large-scale storage of these solid wastes not only occupies valuable land resources, but also causes a series of serious environmental hazards such as soil pollution, water pollution, and dust pollution.

[0003] Throughout the long history of building and decorative materials development, natural stone has always held a prominent position. Over time, the non-renewable nature of the resource has posed challenges to supply stability, prompting a pressing search for a more ideal alternative. This led to the emergence of artificial stone. Conventional artificial stone is produced using concrete, mortar, and other materials. This method not only limits its application scenarios, but also involves high energy consumption and significant emissions of greenhouse gases such as carbon dioxide during the entire production process. While a number of solid waste-based artificial stone products exist, significant technical limitations exist. The tailings used are typically larger than 2.36 mm in particle size, while a significant amount of unused, accumulated tailings is less than 60 microns, resulting in low resource utilization. Furthermore, the production process suffers from long demolding cycles and significant limitations in product workability and mechanical properties. These challenges have made the development of artificial stone production technologies that can fully utilize a variety of solid wastes an urgent need within the industry. This is crucial for promoting the resource utilization of solid waste and reducing the environmental impact of production processes. Summary of the Invention

[0004] In view of this, the present invention aims to overcome the defects in the prior art and proposes a multi-solid waste-based artificial stone and a preparation method thereof.

[0005] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0006] The present invention provides a method for preparing multi-solid waste-based artificial stone, comprising the following steps:

[0007] Step 1 is to mix iron ore tailings powder, fly ash, steel slag powder and water uniformly, and then crush and roll to obtain spherical particles;

[0008] Step 2 is to mix the spherical particles, steel slag powder, fly ash, cement, activator, reinforcing agent and water to obtain wet material;

[0009] Step 3 is to press and shape the wet material, and then cure it to obtain the multi-solid waste-based artificial stone.

[0010] Furthermore, the mass ratio of iron tailings powder, fly ash, steel slag powder and water in step 1 is 70-80:10-20:5-15:5-10; the iron tailings powder in step 1 is made by high-temperature treatment and grinding of iron tailings mud; and the high-temperature treatment step is 300-400°C.

[0011] Furthermore, the particle size of the iron tailings powder in step 1 is less than or equal to 60 microns; the particle size of the spherical particles in step 1 is 2-10 mm.

[0012] Furthermore, the mass ratio of the spherical particles, steel slag powder, fly ash, cement, activator, reinforcing agent, and water in step 2 is 50-70:10-20:8-18:4-10:3-5:0.5-3:10-18; and the cement in step 2 is P•O 42.5 cement, providing the basic gelling properties for the artificial stone.

[0013] Furthermore, the steel slag powder in step 1 is the same as the steel slag powder in step 2; the steel slag powder has a specific surface area of ​​460-520 m2 / kg. The steel slag powder contains active mineral components in equal mass percentages of 45-60% CaO, 25-35% SiO2, and 5-15% Al2O3.

[0014] The fly ash in step 1 is the same as the fly ash in step 2; the fly ash is secondary fly ash.

[0015] Furthermore, the activator in step 2 is ferric hydroxide, potassium silicate and cesium oxide with a plasmid ratio of 2-3:0.5-1.5:0.3-0.5. The activator generates hydration activity in an alkaline stimulating environment and participates in the hydration reaction, thereby enhancing the strength of the artificial stone and improving its durability. When the activator contacts the aqueous solution of fly ash, steel slag powder and iron tailings, cesium oxide and ferric hydroxide undergo hydration reaction to produce a large amount of hydroxide ions. The hydration activity of the active alumina in the fly ash will be fully stimulated, and it will react with the calcium oxide in the steel slag powder to generate hydrated calcium aluminate. At the same time, under the induction of potassium silicate, the activity of silica in the iron tailings is also stimulated, and it reacts with hydroxide ions and calcium oxide to generate hydrated calcium silicate.

[0016] The reaction formula of the activity excitation reaction of the excitant is as follows:

[0017] Formula (I)

[0018] Formula (II)

[0019] Furthermore, the reinforcing agent in step 2 is a modified nano-lithium salt; the preparation method of the modified nano-lithium salt comprises the following steps: uniformly mixing lithium sulfate, acrylic acid, vitamin C and water, heating the obtained mixed solution, dropwise adding a polyether solution and a silane coupling agent thereto, and then heat-insulating to obtain the modified nano-lithium salt.

[0020] The structure of the modified nano lithium salt is shown as follows: Figure 1 As shown. This enhancer can react with calcium aluminate to form Insoluble precipitates can promote the hydration reaction of aluminates and effectively improve the early strength and later stability of artificial stone products.

[0021] The reaction formula of the enhanced reaction of the modified nano lithium salt is shown in formula (III):

[0022] Formula (III)

[0023] As can be seen from the above-mentioned excited reaction, activated alumina and calcium oxide can react to generate calcium aluminate hydrate under the action of an activator, but the reaction is slower, and the calcium aluminate hydrate has a smaller density and a lower strength, so a reinforcing agent is introduced to improve the mechanical properties of the hydrated product. Lithium sulfate can react with calcium aluminate hydrate to generate an insoluble precipitate, and the precipitate density is large. Meanwhile, along with the generation of the precipitate, activated alumina is gradually consumed, thereby accelerating the forward reaction rate of activated alumina and calcium oxide. Due to the widespread use of polycarboxylic acid admixtures, and the poor intermiscibility of inorganic salts such as lithium sulfate and polycarboxylic acid admixtures, the present invention is modified for lithium sulfate, and while ensuring the lithium sulfate strengthening effect, its intermiscibility with the polycarboxylic acid admixture is improved.

[0024] Furthermore, the mass ratio of the lithium sulfate, acrylic acid, vitamin C, water, polyether solution and silane coupling agent is 25-40:5-20:0.5-1.5:60-90:850-1000:3-8; the polyether solution is prepared by mixing 400-450g of polyether and 480-550g of water; the temperature of the heating step is 55-65°C; and the time of the insulation step is 1-1.5 hours.

[0025] Furthermore, the pressure of the pressing step in step 3 is 25-35 MPa; the curing in step 3 is steam curing at 60-70° C. for 20-26 hours.

[0026] The present invention also provides a multi-solid waste-based artificial stone prepared by the preparation method.

[0027] Compared with the prior art, the present invention has the following advantages:

[0028] The multi-solid waste-based artificial stone described in the present invention is prepared by using iron tailings, steel slag and fly ash, which not only consumes a large amount of various solid wastes, reduces the amount of natural sand mined, reduces the emission of polluting gases generated by sintering of cementitious materials, and improves the ecological environment; at the same time, the artificial stone has high toughness, high strength and high wear resistance. After the action of an activator and an intensifier, it can quickly undergo a hydration reaction in a short time to generate gel products such as silicate and aluminate, reduce the internal pore structure, and improve the density, which can reduce the water absorption of artificial stone products and enhance their weathering resistance.

[0029] The multi-solid waste-based artificial stone of the present invention can realize resource utilization of solid waste and reduce the production cost of artificial stone. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Schematic diagram of the structure of the modified nano lithium salt according to an embodiment of the present invention;

[0031] Figure 2 This is a physical picture of the multi-solid waste-based artificial stone described in an embodiment of the present invention. DETAILED DESCRIPTION

[0032] Unless otherwise defined, the technical terms used in the following examples have the same meanings as commonly understood by those skilled in the art to which this invention belongs. The experimental reagents used in the following examples, unless otherwise specified, are conventional biochemical reagents; the experimental methods described, unless otherwise specified, are conventional methods.

[0033] The activator described in each embodiment and comparative example of the present invention is prepared by mixing ferric hydroxide, potassium silicate and cesium oxide in a mass ratio of 3:1:0.5.

[0034] The preparation method of the enhancer described in each embodiment and comparative example of the present invention comprises the following steps:

[0035] 37 g of lithium sulfate, 7 g of acrylic acid and 1 g of vitamin C were uniformly mixed in 72 g of water, and the mixed solution was heated to 60° C. The mixed solution was added dropwise to a polyether solution at 60° C. (the polyether solution was prepared by mixing 420 g of polyether and 510 g of water) within 2 hours. At the same time, 5 g of a silane coupling agent was added dropwise. After the addition was completed, the mixture was kept warm for 1 hour to obtain the reinforcing agent.

[0036] The iron tailings mud described in each embodiment of the present invention and the comparative example was subjected to a high temperature treatment at 370° C. and ground to obtain ultrafine iron tailings powder with a particle size of no more than 60 μm.

[0037] The steel slag powder described in the various embodiments and comparative examples of the present invention is made by grinding waste slag produced during the steelmaking process, and has a specific surface area of ​​460-520 m2 / kg. The steel slag powder contains active mineral components in equal mass percentages of 55% CaO, 35% SiO2, and 10% Al2O3.

[0038] The present invention will be described in detail below with reference to the embodiments.

[0039] Example 1

[0040] A method for preparing multi-solid waste-based artificial stone comprises the following steps:

[0041] Step 1 is to mix 70 parts of iron ore tailings powder, 13 parts of fly ash, 15 parts of steel slag powder and 10 parts of water, and then crush and roll to obtain spherical particles with continuous gradation of 2-10 mm;

[0042] Step 2 is to mix 50 parts of spherical particles, 12 parts of steel slag powder, 10 parts of fly ash, 6 parts of cement, 4 parts of activator, 3 parts of reinforcing agent and 10 parts of water to obtain a wet material;

[0043] Step 3 is to press the wet material into shape at 30 MPa and cure it at 65° C. for 24 hours to obtain the multi-solid waste-based artificial stone.

[0044] Example 2

[0045] A method for preparing multi-solid waste-based artificial stone comprises the following steps:

[0046] Step 1 is to mix 80 parts of iron ore tailings powder, 15 parts of fly ash, 10 parts of steel slag powder and 10 parts of water, and then crush and roll to obtain spherical particles with continuous gradation of 2-10 mm;

[0047] Step 2 is to mix 60 parts of spherical particles, 15 parts of steel slag powder, 15 parts of fly ash, 8 parts of cement, 5 parts of activator, 2 parts of reinforcing agent and 12 parts of water to obtain a wet material;

[0048] Step 3 is to press the wet material into shape at 30 MPa and cure it at 65° C. for 24 hours to obtain the multi-solid waste-based artificial stone.

[0049] The only difference between Comparative Example 1 and Example 1 is that the activator is sodium silicate.

[0050] The only difference between Comparative Example 2 and Example 1 is that the reinforcing agent is calcium formate.

[0051] The only difference between Comparative Example 3 and Example 1 is that the activator is sodium silicate and the reinforcing agent is calcium formate.

[0052] Comparative Example 4

[0053] A method for preparing multi-solid waste-based artificial stone comprises the following steps:

[0054] Step 1 is to mix 70 parts of untreated iron tailings mud, 13 parts of fly ash, 15 parts of steel slag powder and 10 parts of water, and then crush and roll to obtain spherical particles with a continuous grade of 2-10 mm;

[0055] Step 2 is to mix 50 parts of spherical particles, 12 parts of steel slag powder, 10 parts of fly ash, 6 parts of cement, 4 parts of activator, 3 parts of reinforcing agent and 10 parts of water to obtain a wet material;

[0056] Step 3 is to press the wet material into shape at 30 MPa and cure it at 65° C. for 24 hours to obtain the multi-solid waste-based artificial stone.

[0057] The artificial stones obtained from the various examples and comparative examples were subjected to compressive and flexural strength tests. The compressive strength test used a 150 mm cube specimen, while the flexural strength test used a 150 mm × 150 mm × 600 mm rectangular parallelepiped specimen. The specimens were placed in a compression testing machine and a flexural testing machine, respectively, for compression and flexural strength testing. The compressive and flexural strength results were calculated as the arithmetic average of the strengths of three specimens tested simultaneously at the same time. The specific data are shown in Table 1.

[0058] Table 1 Data results

[0059]

[0060] As shown in Table 1, the artificial stone prepared by the present invention by using multiple solid waste-based materials, homemade activators and reinforcing agents has a compressive strength higher than that of ordinary artificial stones by more than 10%, a flexural performance improved by more than 20%, and a water absorption rate reduced by 30%. This is because the homemade activator effectively activates the mineral activity of iron tailings and fly ash, and produces a hydration reaction with steel slag powder to generate a hydrated gel product, and under the action of the modified reinforcing agent, the The amount of production is increased, thereby improving the mechanical properties of the artificial stone. Comparative Examples 1, 2, and 3 all show low strength and high water absorption. This is because, in the solid waste-based system, the ordinary stimulant has a poor activation effect on the solid waste material and cannot effectively cause the solid waste material to undergo a hydration reaction. In addition, the ordinary reinforcing agent has poor compatibility with the polycarboxylic acid admixture and is easily unevenly dispersed in the artificial stone system, resulting in an unclear strengthening effect. Comparative Example 4 shows that when the iron tailings mud is not subjected to high-temperature treatment and is directly applied to the artificial stone system, the prepared artificial stone not only has poor mechanical properties, but also significantly increases its water absorption. This is because, when the iron tailings mud is not subjected to high-temperature treatment, its mineral activity is low, and even under the action of the stimulant, its hydration reaction rate is extremely slow, resulting in a small amount of hydration products generated. The internal structure of the artificial stone is loose and porous, so the artificial stone has low strength and a large water absorption rate.

[0061] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing multi-solid waste-based artificial stone, characterized by: The steps include: Step 1 is to mix iron ore tailings powder, fly ash, steel slag powder and water uniformly, and then crush and roll to obtain spherical particles; Step 2 is to mix the spherical particles, steel slag powder, fly ash, cement, activator, reinforcing agent and water to obtain a wet material; Step 3 is to press and shape the wet material, and then cure it to obtain the multi-solid waste-based artificial stone; The activator in step 2 is ferric hydroxide, potassium silicate and cesium oxide in a mass ratio of 2-3:0.5-1.5:0.3-0.5; The reinforcing agent in step 2 is a modified nano-lithium salt; the preparation method of the modified nano-lithium salt comprises the following steps: uniformly mixing lithium sulfate, acrylic acid, vitamin C and water, heating the obtained mixed solution, dripping a polyether solution and a silane coupling agent therein, and then heat-insulating to obtain the modified nano-lithium salt.

2. The method for preparing multi-solid waste-based artificial stone according to claim 1, characterized in that: The mass ratio of the iron tailings powder, fly ash, steel slag powder and water in step 1 is 70-80:10-20:5-15:5-10; the iron tailings powder in step 1 is prepared by high-temperature treatment and grinding of iron tailings mud; and the temperature of the high-temperature treatment is 300-400°C.

3. The method for preparing multi-solid waste-based artificial stone according to claim 1, characterized in that: The particle size of the iron tailings powder in step 1 is less than or equal to 60 microns; the particle size of the spherical particles in step 1 is 2-10 mm.

4. The method for preparing multi-solid waste-based artificial stone according to claim 2, characterized in that: The mass ratio of the spherical particles, steel slag powder, fly ash, cement, activator, enhancer and water in step 2 is 50-70:10-20:8-18:4-10:3-5:0.5-3:10-18; the cement in step 2 is P•O 42.5 cement.

5. The method for preparing multi-solid waste-based artificial stone according to claim 4, characterized in that: The steel slag powder in step 1 is the same as the steel slag powder in step 2; the specific surface area of ​​the steel slag powder is 460-520 m2 / kg.

6. The method for preparing multi-solid waste-based artificial stone according to claim 1, characterized in that: The mass ratio of the lithium sulfate, acrylic acid, vitamin C, water, polyether solution and silane coupling agent is 25-40:5-20:0.5-1.5:60-90:850-1000:3-8; the polyether solution is prepared by mixing 400-450g of polyether and 480-550g of water; the temperature of the heating step is 55-65°C; and the time of the heat preservation step is 1-1.5 hours.

7. The method for preparing multi-solid waste-based artificial stone according to claim 1, characterized in that: The pressure of the pressing step in step 3 is 25-35 MPa; the curing in step 3 is steam curing at 60-70° C. for 20-26 hours.

8. A multi-solid waste-based artificial stone prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Iron tailing-based artificial high-strength fine aggregate and preparation method thereof

    CN116751018A

  • Early-strength high-fluidity cement-based grouting material and preparation method thereof

    CN119528495A